UJI TINGKAT KONTAMINASI EKSPLAN Centella asiatica (L.) Urban (Pegagan) DALAM KULTUR IN VITRO MELALUI PERBANDINGAN DUA METODE STERILISASI - Kartika Salam Juarna (Jurnal Pro-Life, 2016)
Research has been conducted to determine the effect of sterilizer combination to the contamination level of Pegagan’s (Centella asiatica L. Urban ) explant. Lamina and petiolus were used as an explant. Sterilizer combination is divided into two groups; Methods 1 (M1) and Methods 2 (M2). M1 consists of 0,5% Tetracycline solution, 0,3% Bayclean solution, 0,7% Dithane suspension, 0,3% Tetracycline solution, and aquadest. Meanwhile, M2 consists of Dettol solution, alkohol 70%, 20% Bayclean solution, 0,3% Dithane suspension, and Aquadest. The difference of both methods were on the presences of antibiotics (Tetracycline) in M1 and desinfectans (Bayclean) in M2. Research shows that lamina sterilized by M2 has less contamination than M1, although the petiolus show the same level of contamination. It is believed to be related to the structure that makes lamina contaminated easily.